Approaches to manage 'affordability' of high budget impact medicines in key EU countries. Issue 1 (1st January 2018) - Flume, Mathias; Bardou, Marc; Capri, Stefano; Sola-Morales, Oriol; Cunningham, David; Levin, Lars-Ake; Postma, Maarten J.; Touchot, Nicolas
ABSTRACT: Background: The launch of hepatitis C (HCV) drugs such as sofosbuvir or ledipasvir has fostered the question of affordability of novel high budget impact therapies even in countries with high domestic product. European countries have developed a variety of mechanisms to improve affordability of such therapies, including 'affordability thresholds', price volume agreements or caps on individual product sales, and special budgets for innovative drugs. While some of these mechanisms may help limit budget impact, there are still significant progresses to be made in the definition and implementation of approaches to ensure affordability, especially in health systems where the growth potential in drug spending and/or in the patient contribution to health insurance are limited. Objectives: In this article, we will review how seven countries in western Europe are approaching the question of affordability of novel therapies and are developing approaches to continue to reward new sciences while limiting budget impact. We will also discuss the question of affordability of cost-effective but hugely expensive therapies and the implications for payers and for the pharmaceutical industry.Results: There is clearly not one solution that is used consistently across countries but rather a number of 'tools' that are combined differently in each country. This illustrates the difficulty of managing affordability within different legal frameworks and within different health care system architectures.